Cimetidine as an effective corrosion inhibitor for mild steel in hydrochloric acid - Singh A.; Gupta A.; Rawat A.K.; Ansari K.R.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
The performance of Cimetidine (2-cyano- 1-methyl- 3-(2-[(5-methyl- 1H-imidazol- 4-yl)methylthio]ethyl)guanidine) as corrosion inhibitor for mild steel in 1 M HCl was thoroughly investigated by weight loss and electrochemical methods. The inhibition efficiency of cimetidine obtained by all methods was in good agreement with each other. Polarization studies revealed that the inhibiting action of the cimetidine is under mixed control. The free energy of adsorption and the influence of temperature on the adsorption of inhibitor onto mild steel surface have been reported. The quantum chemical calculations were applied to elucidate adsorption pattern of inhibitor molecules on the steel surface. © 2014 The Authors.